PROPORSIONALITAS DALAM KONTRAK BISNIS WARALABA KLINIK GIGI DI INDONESIA CONTOH KASUS ODAC FAMILY - Wahyuono, Dzaki Dhiya Ulhaq (Ensiklopedia of Journal, 2025)
Abstract: This study examines contractual imbalances in dental clinic franchise agreements, focusing on the legal relationship between franchisor and franchisee. Using a normative juridical approach and a case study of ODAC Family, the research finds that many franchise contracts are unilaterally drafted, lacking proportionality, and structurally disadvantage franchisees. The study proposes practical solutions such as open negotiation, balanced rights and obligations, involvement of professional associations, and independent oversight of contracts. These measures aim to create a fairer and more sustainable contractual relationship within healthcare franchises.Keywords: Franchise, Proportionality, Dental Clinic